How do digital influencers and social presence impact customer’s purchase intention in live streaming commerce, considering the mediating role of customer trust? - Wanda Novita; Fransisca Laij (Universitas Dharmawangsa, 2024)
This research aims to investigate how digital influencers and social presence impact consumer interest in live streaming commerce in Indonesia, with customer trust playing a mediating role. The study utilizes a quantitative approach, collecting data through online questionnaires distributed via Google Form. The population consists of consumers who have engaged in online purchases through live streaming commerce. Purposive sampling yielded 258 respondents. Data analysis employed the partial least squares structural equation model (PLS-SEM) using SmartPls3.0. Findings indicate that digital influencers influence customer trust, social presence affects both customer trust and purchase intention, and customer trust mediates the relationship between social presence and purchase intention.